Effects of pollution and metazoan parasites on the health and oxidative stress biomarkers of two cyprinid fish species in the Olifants River System, South Afrrica - Ramalepe, Tshepiso Promise (University of Limpopo, 2015)
The unprecedented expansion in human population and industry, since the industrial revolution in the late 1700s, has led to increased anthropogenic activities which have indisputably impacted freshwater ecosystems and biological communities therein, including fish. Although this has understandably been the focus, under natural aquatic conditions, no organism is only affected by pollution. Parasites have also been shown in a number of interdisciplinary studies to affect the health of aquatic hosts (amphibians, crustaceans, fish, and mammals). This is illustrated in a number of comprehensive studies the detrimental effects parasites exacerbate when their hosts (fish) are stressed. Therefore, the ability of parasites to interact with anthropogenic stressors, as well as effects they have on the genetic, cellular or tissue level of their host is crucial in conservation and sustaining aquatic biodiversity. As such, the present study examined the combined effects of pollution and metazoan parasites on the health and oxidative stress biomarkers, evaluated for the first time for silver carp, Hypophthalmichthys molitrix (Valenciennes, 1844) and rednose mudfish, Labeo rosae Steindachner, 1894, in one of South Africa’s impacted freshwater ecosystems, Flag Boshielo Dam, Olifants River System, Limpopo Province. Seasonal surveys were conducted from February 2012–January 2013. A total of 111 H. molitrix and 116 L. rosae fish specimens were collected using conventional angling gear, scoop and gill nets with stretched mesh sizes of 30–110 mm. The two selected cyprinid fish species were assessed for oxidative stress biomarkers [Glutathione S-transferase (GST), lipid peroxidation (MDA) and Total Antioxidant Capacity (TAC)] and parasitism of metazoan parasites. Concentrations of biomarkers of oxidative damage and antioxidant defense in the gill and liver tissue were measured to assess how these major organs of the immune system responded to oxidative stress associated with parasitic infections. In addition, water quality analyses were carried out by testing an assay of physico-chemical parameters to establish the level of contamination. Fish health was assessed using the Health Assessment Index (HAI), refined Parasite Index (PI), Inverted Parasite Index (IPI) and Condition Factor (K) protocols. Relative to previous studies at Flag Boshielo Dam, water quality results showed an increase of nutrients, major ions and several metals which may have adverse effects that may comprise fish health; however, this dam remains moderately polluted in a mesotrophic state. The fish health assessment results indicated that H. molitrix was more affected in terms of the necropsy and parasite based assessments (HAI, IPI and K) with mean±SD of 65.68±35.51; 68.29±25; 0.82±0.20, respectively, as compared to 39.14±22.44; 28.79±18.33; 1.17±0.21 for L. rosae during the study. In addition, significantly higher parasitic infections (mean prevalence of infection with any species of parasite = 45.3±0.13) were observed for H. molitrix than L. rosae (12.0±0.05). Furthermore, there was considerable variation in biomarker concentration between highly infected and non-infected fish, for and between each species and tissues with regard to parasite infection, suggesting that the specific functions of each tissue are associated with their susceptibility to oxidative stress, as well as their ability to defend against oxidative damage. These results illustrate that although fish are affected by aquatic contaminants they are to an extent affected by parasites, which may act synergistically on the health of the two fish species. Most importantly, it was suggested that knowledge on the parasites of alien H. molitrix when compared to indigenous L. rosae may give an indication of how adaptive this fish are to new localities as well as expands the information on the rarely studied biology, epizootiology and ecological interactions of these two cyprinid species. Keywords: Health Assessment Index, refined Parasite Index, Inverted Parasite Index, Condition Factor, water quality, lipid peroxidation, Glutathione S-transferase, Total Antioxidant Capacity, Hypophthalmichthys molitrix, Labeo rosae, Flag Boshielo Dam.
Thesis (M. Sc. (Zoology)) -- University of Limpopo, 2015
Keywords: Health assessment index; Refined paradise index; Inverted paradise index; Condition factor; Water quality; Lipid peroxidation; Glutathione S-transferase; Total antioxidant capacity; Hypophthalmichthys molitrix; Labeo rosae; Flag Boshielo Dam; 577.6; Freshewater ecology; Ecology